Cultural Pluralist Perspective: Assessing the Functions of Ethno-Religious Politics in the Philippines - Taya, Shamsuddin L; Macasayon, Mocamad M; Lantong, Abdul M; Ali, Abubakar L (FISIP Universitas Malikussaleh, 2021)
Any general effort to account for the role of ethno-religiosity in the Philippines raises the question of the dominant role ethnoreligious politics has taken. Thus, the purpose of this article is to examine and analyze the role of ethnoreligious politics in the Philippines, using the Cultural Pluralist perspective. To this theory, the melting pot has never eradicated ethnoreligious politics in any given country. Â It is divided into three parts. Firstly, it deals with the economic function of ethnoreligious politics in the region. Secondly, it looks into the psychological role of ethnoreligious politics. Lastly, examines the civic role of ethnoreligious politics in the Philippines. As shown in this article, many people in the Philippines have been unified from time to time by ethnoreligious bonds and used politics to secure material goals, to satisfy their psychic needs, and on occasion, to bring about fundamental changes in their civic values. Therefore, it is clearly indicated that ethnoreligious politics serves as a tool in achieving their material desires, psychological needs and recognition of their civic values.AbstrakSetiap upaya umum dalam menjelaskan pengaruh etnoreligiusitas di Filipina menimbulkan pertanyaan mendasar tentang peran dominan yang diambil oleh politik etnoreligius. Dengan demikian, tujuan artikel ini adalah mengkaji dan menganalisis peran politik etnoreligius di Filipina dengan menggunakan perspektif Kultural Pluralis. Menurut teori ini, politik etnoreligius tidak dapat dihapuskan di negara mana pun. Hal ini berhubungan dengan tiga hal pokok. Pertama, berkaitan dengan fungsi ekonomi politik etnoreligius di wilayah tersebut. Kedua, melihat peran psikologis politik etnoreligius. Terakhir, mengkaji peran politik sipil etnoreligius di Filipina. Seperti yang ditunjukkan dalam artikel ini, banyak orang Filipina telah dipersatukan dari waktu ke waktu oleh ikatan etnoreligiusitas dan menggunakan politik etnoreligius untuk mengamankan tujuan material, memenuhi kebutuhan psikis, dan kadangkadang membawa perubahan mendasar dalam nilai-nilai kewarganegaraan mereka. Oleh karena itu, diindikasikan bahwa politik etnoreligius berfungsi sebagai alat untuk mencapai berbagai kepentingan dari para penganutnya.